Study of polymorphism of Growth Hormone-releasing Hormone (GHRH) Alleles in Iranian Sarabi Cows - mehdi khosravi; mehdi aminafshar; mohammad chamani (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2013)
Selection based on molecular markers is one of the new methods that may improve progress and accuracy of selection in animal breeding programs. The GHRH gene (Growth Hormone-releasing Hormone) is a candidate gene for marker-assisted selection strategies. Polymorphs of GHRH gene are reported to be significantly associated with milk production and constituent traits. In order to study the polymorphism of GHRH gene, blood samples were collected from 112 Sarabi cows. Genomic DNA was extracted and a fragment of 297 bp in size was amplified using polymerase chain reaction. The amplified fragments were subjected to restriction digestion with HaeIII endonuclease enzyme and the resultant digested products were run on 2% Agarose gel. The results revealed the existence of two alleles of GHRH A and GHRH B for the examined locus with frequencies of 0.19 and 0.81 respectively. Three different genotypic variants including GHRH A GHRH A, GHRH A GHRH B and GHRH B GHRH B were identified with genotypic frequencies of 0.0357, 0.3037 and 0.6607 respectively. The χ2 test showed that population is in Hardy-Weinberg equilibrium (P